The Application of Sport Tourism as An Out-Of-Class Learning Medium in Improving Sportsmanship and Cooperation of Elementary School Students - Purba, Joen Parningotan; Payung, Milda Vinna br (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This study aims to explore the effectiveness of the application of sport tourism as a learning medium outside the classroom in increasing sportsmanship and cooperation of elementary school students. Sport tourism as a learning approach combines physical activity and exploration of the natural environment with character education values, thereby encouraging the creation of active, collaborative, and meaningful learning experiences. This study uses a quantitative method with a pre-experimental design (one group pretest-posttest design), involving 30 grade IV students in one of the elementary schools in Samosir Regency. Data was collected through a sportsmanship attitude questionnaire and a group cooperation observation sheet. The results of the study showed a significant increase in student sportsmanship and cooperation scores after participating in sports tourism activities as an out-of-class learning medium. These findings indicate that sport tourism can be an effective medium in fostering positive character values of elementary school students, as well as strengthening social skills through direct experiences outside the formal school environment. This activity also supports the implementation of the Independent Curriculum and project-based learning that emphasizes strengthening the Pancasila Student Profile.